Bacteria-targeting photoactivated antibacterial nanosystem based on oligoalginate-protoporphyrin IX for plant disease treatment. (5th October 2022) - Liu, Jinsheng; Dai, Zhuoer; Shen, Pingkai; Yin, Yihua; Yi, Yin; Cai, Weiquan; Fan, Lihong; He, Guanghua; Zhang, Jingli; Xu, Wenjin; Chen, Silin; Pan, Jiayi
Graphical abstract: Highlights: Novel antibacterial system was constructed based on alginate oligosaccharide -PpIX. The photodegradation of PpIX was effectively inhibited by fluorescence quenching. GSH-triggerd photodynamic antibacteria and bacteria-targeting were observed. The significantly enhanced inhibition effect on pathogenic bacteria was detected. The system shows great potential for plant disease control. Abstract: To enhance bacteria-targeting and improve bactericidal activity, a novel GSH-responsive photodynamic antimicrobial nanosystem based on Alginate oligosaccharide-protoporphyrin IX (AOS-ss-PpIX) conjugates were constructed. The fluorescence self-quenching caused by the aggregation of PpIX groups into hydrophobic core could promote the photostability of PpIX and avoid the phototoxicity of the non-infected sites of the target plants. But once exposed to GSH stimulus, the recovery of high photodynamic activity were observed due to the destruction of the system and accompanied by the release of thiolated PpIX, and the photodynamic activity after 2 h was higher than that of PpIX under the same conditions. Furthermore the system showed more efficient photodynamic antibacterial capacity under light exposure. Moreover, the pot experiment also verified that the system showed outstanding control efficacy against cabbage soft rot caused by Erwinia carotovora Sclerotinia. Safety test exhibited that the size of nanoparticles can restrict the entry of nanoparticles into the plant cells to trigger photocytotoxicity. The design strategy provides a platform for promoting the utilization of photoactivated pesticides and reducing or avoiding their harm to target plants and the environment.